The Social Dynamics of Village Communities: A Case Study on the Implementation of Improved Access to Clean Water in Wargasaluyu Village - Khutomah, Dewi Ajeng; Pirngadi, Budi Heri; Syarifudin, Deden (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
Wargasaluyu Village, located in Gununghalu District, West Bandung Regency, has historically faced limited access to clean water. In mid-2023, a group of students participating in the Perguruan Tinggi Mandiri Membangun Desa (PTM2D) program initiated a project to improve clean water access for the Wargasaluyu village community. This research examines the short-term outcomes of implementing improved clean water access on the social dynamics of the Wargasaluyu Village community. The study aims to identify the social dynamics that have emerged in the Wargasaluyu Village community as a short-term outcome of this implementation. The analytical methods employed were triangulation and descriptive-analytical approaches. Results indicate that the quality, quantity, and continuity of clean water underwent significant improvements, becoming feasible and safe, and subsequently effecting changes in the community's social dynamics. Significant direct changes experienced by the community include shifts in mindset and participation, increased spirit of cooperation, enhanced community organization, and improved utilization of social infrastructure through mutual care, thereby facilitating the implementation of improved welfare levels. These direct changes contribute to indirect changes, namely alterations in employment, income levels, community welfare, and village independence. The social dynamics occurring in the Wargasaluyu Village community affect not only social aspects but also will give impact educational, health, economic, cultural, and environmental dimensions. This research provides insights not only for more effective improvements in clean water access but also for holistic village water management that addresses community needs and aspirations, aiming to achieve sustainable and inclusive rural development in Wargasaluyu Village.